(untitled) (The Review of Diabetic Studies, 2024)
Background: Telepharmacy offers a novel approach to chronic disease management by enhancing medication adherence, patient engagement, and access to care. Methods: This study evaluated 200 patients enrolled in telepharmacy programs. Clinical outcomes (HbA1c, blood pressure), medication adherence, patient engagement, satisfaction, and technology acceptance were assessed. Analyses included paired t-tests, ANOVA, correlations, moderation, and multivariate regression (p < 0.05). Results: Telepharmacy implementation led to significant improvements in glycemic control (HbA1c: −0.81%, d = 0.69) and blood pressure (systolic: −11.6 mmHg, d = 0.58; diastolic: −7.5 mmHg, d = 0.53), with over 90% of participants achieving stable or improved outcomes. Medication adherence, patient engagement, and technology acceptance significantly predicted clinical improvements, explaining 38% of HbA1c variance. High engagement (M = 4.42) and satisfaction (M = 4.56), as well as strong perceived usefulness (M = 4.38) and ease of use (M = 4.31), were reported. Telepharmacy enhanced access-to-care, particularly in rural and underserved areas. Conclusions: Telepharmacy effectively improves clinical outcomes, promotes adherence, and enhances patient engagement and access to care, with technology acceptance serving as a key facilitator. These findings support telepharmacy as an integrated and scalable model for chronic disease management.